Postmenopausal estrogen receptor positive breast cancer and obesity associated gene variants - Ozgoz, Asuman; Tütüncü, İlknur; İçduygu, Fadi̇me Mutlu; Yukselturk, Aysegul; Şamli, Hale; Ozturk, Kuyas Hekimler; Baskan, Zuhal (IfADo - Leibniz Research Centre for Working Environment and Human Factors, Dortmund, 2021)
Obesity is one of the most important health risks in postmenopausal women. Molecular pathways that are connected with obesity are believed to interact with the pathogenesis of breast cancer (BC). The aim of this research was to study the polymorphisms of two obesity-associated genes ADIPOQ and FTO that are also related to the pathogenesis of BC. Obesity-associated gene polymorphisms ADIPOQ rs1501299 and rs2241766, and FTO rs1477196, rs7206790, rs8047395, and rs9939609 were studied in 101 Turkish postmenopausal estrogen receptor-positive BC patients and 100 healthy control individuals. ADIPOQ rs1501299 was detected to be associated with protection against BC. The ADIPOQ rs1501299 TT genotype, the rs2241766 GT genotype and the G allele were found to be significantly higher in the control group. In addition, ADIPOQ rs1501299 polymorphism was protective in the recessive model and rs2241766 polymorphism was protective in the dominant model. While none of the FTO gene polymorphisms were found to be associated with BC, the frequencies of rs9939609 A allele and rs7206790 G allele were correlated with body mass index (BMI) in BC patients. ADIPOQ rs1501299 TT genotype, rs2241766 GT genotype, and G allele might be protective against BC in the Turkish population but this conclusion needs to be further verified.

EXCLI Journal; 20:Doc1133; ISSN 1611-2156
Keywords: postmenopausal; breast cancer; ADIPOQ; Original Article; FTO; polymorphism; 2. Zero hunger; 3. Good health